Inovasi Alat Pengering Elektrik Emping Melinjo (Kepingjo) Untuk Membantu Meningkatkan Produksi Skala Rumah Tangga - Suardi, Suardi; Susilo, Hendra; Muchlishiin, Moh.; Ndruru, Andreas F.; Gulo, Syukur A. (STMIK Royal, 2025)
Abstract: This community service activity was motivated by the drying problems of emping melinjo in Perbaungan District, Serdang Bedagai Regency, which still relies on sunlight. This traditional method has many limitations as it depends on weather conditions, requires 2–3 days, and produces products that are less hygienic and inconsistent in quality. The purpose of this activity is to provide a solution through mentoring and training in the use of the electric emping melinjo dryer (KEPINGJO) so that partners are able to operate the equipment and increase production capacity. The implementation method includes several stages: preparation, technology socialization, training, trials, evaluation, and mentoring. The results show that the partners actively participated and were able to operate the equipment independently. The use of the electric dryer resulted in a reduction from 1 kg to 0.64 kg within 1 hour at a temperature of 55 °C, which is much faster than the traditional drying method that takes 2–3 days. In addition, the moisture content of emping melinjo, initially 29% in the wet condition, decreased to 9.5% after the drying process using the electric dryer. The final product is more hygienic, evenly dried, and has a longer shelf life. The application of the KEPINGJO electric dryer has proven to increase productivity, product quality, and household income while strengthening the role of universities in delivering appropriate technological innovations. Keywords: dryer; melinjo; empowerment; training; food self-sufficiency Abstrak: Kegiatan pengabdian kepada masyarakat ini dilatarbelakangi oleh permasalahan pengeringan emping melinjo di Kecamatan Perbaungan, Kabupaten Serdang Bedagai, yang masih mengandalkan sinar matahari. Metode tersebut memiliki banyak keterbatasan karena bergantung pada cuaca, membutuhkan waktu 2–3 hari, serta menghasilkan produk yang kurang higienis dan tidak seragam. Tujuan kegiatan adalah memberikan solusi melalui pendampingan dan pelatihan penggunaan alat pengering elektrik emping melinjo (KEPINGJO) agar mitra mampu mengoperasikan dan meningkatkan kapasitas produksi. Metode pelaksanaan meliputi tahap persiapan, sosialisasi teknologi, pelatihan, uji coba, serta evaluasi dan pendampingan. Hasil kegiatan menunjukkan mitra aktif berpartisipasi dan mampu menggunakan alat secara mandiri. Penggunaan alat pengering elektrik memperlihatkan penyusutan dari 1 kg menjadi 0,64 kg dalam waktu 1 jam pada suhu 55 °C, jauh lebih cepat dibanding metode tradisional 2–3 hari. Selain itu, kadar air emping melinjo yang semula sebesar 29% pada kondisi basah menurun menjadi 9,5% setelah proses pengeringan menggunakan alat pengering elektrik. Produk yang dihasilkan lebih higienis, kering merata, dan memiliki daya simpan lebih lama. Penerapan pengering elektrik KEPINGJO terbukti meningkatkan produktivitas, kualitas, serta pendapatan rumah tangga, sekaligus memperkuat kontribusi perguruan tinggi dalam menghadirkan inovasi tepat guna. Kata kunci: alat pengering; melinjo; pemberdayaan; pelatihan; kemandirian pangan